Fracture resistance of fixed partial dentures: the influence of restoration geometry and material in additive manufacturing - Kavvas-Celik, Ezgi; Comert, Zekeriya Yasar; Alpkilic-Issever, Dilara Seyma; Ongul, Deger; Kelesoglu, Ergun; Isler-Deger, Sabire (KOREAN ACAD PROSTHODONTICS, 2025)
PURPOSE. The location of the edentulous area in the dental arch can influence the design of the bridge prosthesis in the surrounding region and the forces it will encounter. This study assessed the fracture strength of restorations with various geometric designs produced using different additive and subtractive manufacturing methods. MATERIALS AND METHODS. Co-Cr metal and zirconia fixed partial denture (FPD) frameworks were designed in both linear and curved geometries. The Co-Cr metal frameworks were produced through casting (C) and laser sintering (L), while the zirconia (Z) frameworks were obtained through milling (n = 10). After veneering the frameworks, a four-point bending test was conducted on the specimens to assess their fracture strength. All obtained values were statistically analyzed (P < .05). RESULTS. In both linear and curved groups, Z group showed the lowest fracture resistance values followed by C and L groups and the differences between the groups were found statistically significant (P < .05). In L group, curved FPDs showed statistically significantly higher fracture resistance values than linear FPDs (P < .05). In both Z and C groups, curved FPDs showed statistically significantly lower fracture resistance values than linear FPDs (P < .05). CONCLUSION. The geometric configuration of the restoration and manufacturing technique affects the fracture resistance of different framework materials in FPDs. [J Adv Prosthodont 2025;17:92-100]
Keywords: Additive manufacturing; Fracture resistance; Framework design; Zirconia; METAL-CERAMIC RESTORATIONS; LOAD-BEARING CAPACITY; IN-VITRO; STRENGTH; DESIGNS; ALLOYS; FIT; Dentistry, Oral Surgery & Medicine